Quality of life deterioration and associated factors in prenatal care pregnant women: assessment with the WHOQOL-BREF scale (2023)
Introduction: Quality of life is a set of situations that contribute to people's well-being. In pregnant women, it is necessary to explore the emotional, social and physical aspects. Few studies in the Latin American population explore the quality of life of pregnant women. The objective was to establish the frequency of deterioration of the physical, psychological, social and environmental quality of life and to identify the associated factors in pregnant women residing in cities of the Colombian Caribbean who attended prenatal consultation. Material and methods: A cross-sectional study was conducted on 509 pregnant women who performed daily activities and participated voluntarily and anonymously after signing informed consent. They filled out a form that explored sociodemographic and clinical characteristics and applied the WHOQOL-BREF scale, identifying the poor quality of life. Adjusted logistic regression was performed to estimate the association between quality of life (dependent variable) and biopsychosocial factors (independent variables). Results: The age of the participants was 26.8 ± 6.2 years. In 250 (49.1%) physical or mental deterioration was identified, in 281 (55.2%) deterioration of the social relationship and in 270 (53.0%) of the environmental relationship. Diabetes OR:6.01[95%CI:1.20-18.42], depression OR:4.71[95%CI:1-20-18.42], living in a rural area OR:2.96[95%CI :1.78-4.91], anguish with pregnancy OR:2.87[95%CI:1.65-5.01], financial problems OR:2.61[95%CI:1.54-4.40 ] or couple OR:2.60[95%CI:1.03-6.69], were associated with impaired quality of life (p<0.01). Being cohabiting, compared to being alone, and being a student/employee versus a housewife, were associated with a lower possibility of deterioration in quality of life (p<0.01). Conclusions: Deterioration of each quality of life domain was identified in half of the pregnant women and several biopsychosocial factors were significantly associated. Antenatal care protocols should provide guidelines for intervention on obstetric and non-obstetric factors that impair quality of life. It is necessary to highlight deficiencies in the exploration of the mental, social and environmental health of pregnant women